FC 091URINARY CCL5 MRNA, A POTENTIAL BIOMARKER FOR PROGRESSION OF TYPE 2 DIABETIC NEPHROPATHY. (29th May 2021) - Feng, Songtao; Gao, Yueming; Cao, Jingyuan; Yin, Di; Lv, Linli; Liu, Bicheng
Abstract: Background and Aims: In recent years, it has been found that targeted mRNA detection of sediment cells in urine can be used as novel biomarkers for the diagnosis of diabetic nephropathy (DN). However, its value in predicting the progression of DN is not clear. The purpose of this study is to seek for urinary mRNA markers that evaluate the prognosis of DN through systems biological screening, clinical verification and prospective studies. Method: GEO database and "Nephroseq" platform were searched, and the transcriptome data of DN glomeruli and tubules and their clinical information were obtained. Weighted gene co-expression network analysis (WGCNA) combined with gene ontology (GO) annotation and KEGG pathway enrichment analysis were used to screen the hub genes negatively related to eGFR, and the hub genes were used as candidate markers for mRNA detection in urine sediment in DN patients. A total of 91 patients with DN diagnosed by renal biopsy were included, and 60 patients with type 2 diabetes and 61 healthy people were selected as the control groups. The mRNA expression of candidate molecules was detected by Taqman probe quantitative PCR, and the correlation between mRNA expression and eGFR and urinary protein levels were analyzed. Patients with DN were followed up for a median time of 21 months, and the primary end point was defied as end stage renal disease or eGFR decreasing by more than 50%. Multivariate Cox regression was used to evaluate the value of mRNA in predicting DN progression. Results: GSE30528 and GSE30529 datasets were selected for analysis, including mRNA expression data of 9 cases of DN and 13 cases of normal glomeruli; and 10 cases of DN and 12 cases of normal tubules respectively. The clinical data of the patients in this study, including gender, race, age and eGFR, were searched on the Nephroseq platform. The gene modules negatively related to eGFR were screened by WGCNA. GO and KEGG analysis showed that the main function of the gene modules in both datasets were related to the activation of inflammatory cells and chemokines pathway. Through the screening of hub genes and the comparison of expression levels, CCL5, CXCL1, CXCL6 and CXCL12 were finally obtained as candidate genes. Quantitative PCR showed that the levels of CCL5 and CXCL1 was significantly increased in DN group, CCL5 was negatively correlated with eGFR and positively correlated with urinary protein level, while CXCL1 was negatively correlated with eGFR, but had no significant correlation with urinary protein level. Multivariate Cox regression showed that eGFR, urinary protein level, degree of renal fibrosis and urinary CCL5 were independent risk factors of primary end point. Conclusion: The activation of chemokine signal pathway in renal tissue is involved in the progression of DN. Urinary CCL5 mRNA can independently predict the prognosis of DN and may be served as a novel biomarker for the progression of DN.